The Stigma of the Yutori Generation in the Drama Series “Yutori desu ga nani ka” - Linda Unsriana; Sandy Saputra (IZUMI, 2025)
Yutori education is an educational system designed to reduce student pressure. This relaxed approach has led to the emergence of a new generation known as the "Yutori Generation," which includes individuals born between 1987 and 1996. This generation is depicted in the television drama series "Yutori Desu Ga Nani Ka," directed by Nobuo Mizuta. The objective of this research is to analyze the characteristics of the show's three main characters and to evaluate whether the stigma associated with them is accurate. The writer employed a qualitative research methodology. For data gathering, a library research method was used, and the analysis was conducted using a descriptive-analytical approach. The theoretical framework for this study includes the Yutori education theory by Paivi Poukka, the characteristics of the Yutori generation as explained by Hironobu Fujiwara, and Erving Goffman's theory of stigma. The data analysis results indicated that the community's stigmatization of the three characters in the play was not entirely accurate. Keywords: Japanese; Drama, Yutori; Stigma; Generation gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor